Growth performance of pearl goldfish juvenile carassius auratus cultured in 3 ppt salinity with different exposure time of electric field - Nirmala, Kukuh; Armansyah, Rizky; Priyadi, Agus (Indonesian Society of Scientific Aquaculture (ISSA), 2011)
ABSTRACTGrowth rate of pearl goldfish juvenile Carassius auratus relatively slow to reach market size which will take approximately three months. To accelerate its growth can be done by providing exposure of the fish to low-power electric fields (10 V) via 3 ppt salinity water, with the goal of providing the close isoosmotic conditions, and also to streamline the flow of electricity from the electrodes to the body of the fish. This study aims to calculate the survival and growth rate of pearl goldfish juvenile of S sizes (2‒4 cm of body length) which were maintained at 3 ppt salinity water and treated by different exposure time of electric field (zero, two, four, and six minutes before feeding) with 10 volt electric power. Fish were cultured at a density of 2 fish/L in the (20×30×20 cm3) aquaria in volume of 6 L of water. Test fish had an average body length of 4.11±0.05 cm and the average body weight of 2.89±0.05 g. Exposure time of electric field were zero, two, four, and six minutes before the fish are fed, performed every day as much as three times i.e. morning, afternoon, and evening. The research design used was completely randomized design with four treatments, namely 0, 2, 4, and 6 (time for exposure is zero/control, two, four, and six minute) with three replications. The results show test fishes exposed to 10 volt electrical field for zero, two, four, and six minutes, have no significant effect on survival rate (P>0.05). For growth performance, four minute exposure treatment gives the best results compared to controls (P<0.05), supported by an increase in the percentage of the ratio of gut length to body length of the fish and higher feed efficiency.Keywords: long exposure to the electric field, growth performance, pearl goldfishABSTRAKPertumbuhan benih ikan hias maskoki mutiara Carassius auratus relatif lambat, karena untuk mencapai ukuran jual memerlukan waktu sekitar tiga bulan. Untuk mempercepat pertumbuhannya dapat dilakukan dengan pemberian paparan medan listrik berdaya rendah (10 V) ke air media budidaya yang dinaikkan salinitasnya menjadi 3 ppt, dengan tujuan memberikan kondisi mendekati isoosmotik, dan juga untuk mengefektifkan arus listrik dari elektroda ke tubuh ikan. Penelitian ini bertujuan untuk menghitung tingkat kelangsungan hidup dan pertumbuhan benih ikan maskoki mutiara ukuran S (2‒4 cm) yang dipelihara pada media bersalinitas 3 ppt yang diberi perlakuan lama waktu pemaparan medan listrik (nol, dua, empat, dan enam menit sebelum ikan diberi pakan) dengan daya 10 volt. Ikan dipelihara dengan kepadatan 2 ekor/L dalam akuarium berukuran 20×30×20 cm3 dengan volume air 6 L. Ikan uji yang digunakan memiliki panjang rata-rata 4,11±0,05 cm dan bobot rata-rata 2,89±0,05 g/ekor. Pemberian paparan medan listrik dilakukan selama nol, dua, empat, dan enam menit sebelum ikan diberi pakan, dilakukan setiap hari sebanyak tiga kali yaitu pagi, siang, dan sore hari. Rancangan penelitian terdiri atas empat perlakuan, yaitu 0, 2, 4, dan 6 (lama paparan nol/kontrol, dua, empat, dan enam menit) yang diulang masing-masing tiga kali ulangan. Hasil pemaparan arus listrik 10 volt selama nol, dua, empat, dan enam menit, tidak memberikan pengaruh yang nyata pada kelangsungan hidup (p>0,05). Untuk kinerja pertumbuhan, perlakuan paparan empat menit memberikan hasil yang terbaik dibandingkan kontrol (p<0,05), didukung oleh peningkatan persentase nilai rasio panjang usus terhadap panjang tubuh ikan serta nilai efisiensi pakan yang lebih tinggi.Kata kunci: lama paparan medan listrik, kinerja pertumbuhan, ikan maskoki mutiara